52.0k views
0 votes
Perform the indicated operations below and simplify ((a+b)/4) + ((2a-b)/5).

1 Answer

7 votes

Answer:


((a+b))/(4) +((2a-b))/(5)=(13a)/(20) +(b)/(20)

Explanation:

We have:


((a+b))/(4) +((2a-b))/(5)

We can use common denominator.

Observation:

If you have,
(a)/(b) +(c)/(d)=((a*d)+(c*b))/(b*d)

Then,


((a+b))/(4) +((2a-b))/(5)=(5(a+b)+4(2a-b))/(4*5)

Using distributive property:

Observation:

c(a+b)=ca+cb


(5(a+b)+4(2a-b))/(4*5)=(5a+5b+8a-4b)/(20)=((5a+8a)+(5b-4b))/(20)

Finally,


((5a+8a)+(5b-4b))/(20) =(13a+b)/(20)=(13a)/(20) +(b)/(20)

The answer then is:


((a+b))/(4) +((2a-b))/(5)=(13a)/(20) +(b)/(20)

User Renaud Favier
by
6.1k points